Conducting reaction time research in second language studies - Jiang, Nan (Routledge, 2012)
This book offers a general introduction to reaction time research as relevant to Second Language Studies and explores a collection of tasks and paradigms that are often used in such research. It provides a lucid explanation of the technical aspects of collecting reaction time data and outlines crucial research principles and concepts that will ensure accurate data. In addition, Conducting Reaction Time Research in Second Language Studies provides step-by-step instructions for using DMDX, a software program widely used for conducting reaction time research. From general guidelines to techniques to working with data, this complete "why and how" guide for conducting reaction time research is ideal for both students/beginners and more seasoned researchers.